The Discovery of Circadian Rhythm of Feeding Time on Digestive Enzymes Activity and Their Gene Expression in Sinonovacula constricta Within a Light/Dark Cycle - Liu, Yanzi; Yao, Hanhan; Zhou, Tingting; Lin, Zhihua; Dong, Yinghui (Frontiers in Marine Science, 2021)
The circadian rhythm has a great impact on the growth, metabolism and development of animals, but little is known about the circadian rhythm of marine bivalves. Understanding of the feeding rhythm is of great significance to increase the yield of razor clam Sinonovacula constricta, an economically important bivalve mollusk. The aim of this experiment was to study the effects of circadian rhythm of feeding time on digestive enzymes activities and their gene expression in S. constricta within a light (ZT8-ZT20)/dark (ZT20-ZT8) cycle. The present results showed that circadian rhythm of feeding rate (FR) was highly associated with digestive enzyme activities and relative expression of their genes. The highest values of FR were basically observed in the night from ZT0-ZT2 and ZT6-ZT8, which were significantly higher than those values in the daytime from ZT12-ZT14 and ZT18-ZT20 (P < 0.05). The digestive enzymes activities displayed the highest values at ZT2 and ZT8, and the lowest at ZT14 and ZT20. Among them, cellulase and pepsin were found to have significantly different activities (P < 0.05), rather than amylase and lipase. Notably, the relative expression of digestive enzyme genes shared the similar pattern with the activities of digestive enzymes. The highest values of relative gene expression of amylase (AMY), lipase (LIP), cellulase (CEL), and pepsin (PEP) were found at ZT2 and ZT8 in the night, while the lowest values were found at ZT14 during the day. It is therefore suggested that the biological clock may regulate the process from feeding to digestion. Furthermore, it might be better to feed at night to reduce cultivating cost and increase economic benefits in the farming industry of S. constricta.